Large eddy simulation of an onshore wind farm under different operating regimes including topographic effects. Issue 2 (1st May 2022) - Draper, M; López, B; Maiuri, D; Decaro, C; Campagnolo, F
Abstract: High-fidelity simulations of actual wind farms with the Actuator Line Model, in a Large Eddy Simulation framework, have been performed in the past years, for both onshore and offshore sites. It has become the state of the art to simulate the wind flow through wind turbines and wind farms and it could be a powerful tool to assess the operation of actual wind farms and potential improvements. The objective of the present paper is two-fold: develop a high-fidelity numerical model of an onshore wind farm to be used to assess the influence of different environmental and aerodynamic conditions in its power performance and analyze, as case study, the effect of the topography in the wind flow and power production.